Polymicrobial growth in standard urine culture: Time to Act or Ignore?. (April 2022) - Nityadarshini, Neha; Mohapatra, Sarita; Gautam, Hitender; Jain, Vishesh; Chaudhry, Rama; Kapil, Arti
Diagnosing Urinary Tract Infections (UTI) remains a clinical challenge. A monobacterial growth in standard urine culture is diagnostic while polymicrobial growth is usually considered as contaminants. However, in certain cases, true mixed infections may exist making it important to correctly identify the pathogens and streamline the therapy. Communication between the clinician and microbiologist is essential to establish the right diagnosis at right time. Here, we would like to share our experience about a polymicrobial UTI in a paediatric patient in which coordinated discussion between the clinical team and microbiologist was helpful for favourable outcome.